The Gamma Ray Transmission Factor of Spent Fuel - Quan, Nguyen Van; Loat, Bui Van; Tam, Nguyen Cong (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abtract: Passive non-destructive methodswere developed for determining total U, 235 U and total Pu content of damaged spent fuel. The methods based on correlations between 137 Cs and U, Pu content and using referent spent fuel assemblies. It means that the nuclear material content can be derived from measurable 137 Cs content, which depends on gamma ray transmission factor. In this work, this factor was determinedby aninfinite energy method and the same for both damaged and referentspent fuel with error less than 12%. Keywords: Passive non-destructive methods, Damaged spent fuel,Referentspent fuel,Transmission factor, Infinite energy method.